Long covid and medical gaslighting: Dismissal, delayed diagnosis, and deferred treatment - Larry Au; Cristian Capotescu; Gil Eyal; Gabrielle Finestone (Elsevier, 2022)
While we know a lot more about Long Covid today, patients who were infected with Covid-19 early on in the pandemic and developed Long Covid had to contend with medical professionals who lacked awareness of the potential for extended complications from Covid-19. Long Covid patients have responded by labeling their contentious interactions with medical professionals, organizations, and the broader medical system as "gaslighting." We argue that the charge of medical gaslighting can be understood as a form of ontological politics. Not only do patients demand that their version of reality be recognized, but they also blame the experts who hold gatekeeping power over their medical care for producing a distorted version of said reality. By analyzing results from an online survey of Long Covid patients active on social media in the United States (n ​= ​334), we find that experiences of contention and their reframing as "gaslighting" were common amongst our respondents. In short answer responses about their experience obtaining medical care for Long Covid, our respondents described encountering medical professionals who dismissed their experience, leading to lengthy diagnostic odysseys and lack of treatment options for Long Covid. Even though we are limited by characteristics of our sample, there is good reason to believe that these experiences and their contentious reframing as medical gaslighting are exacerbated by gender, class, and racial inequalities.